A model to predict the risk of lethal nasopharyngeal necrosis after re‐irradiation with intensity‐modulated radiotherapy in nasopharyngeal carcinoma patients. Issue 1 (29th June 2016) - Yu, Ya‐Hui; Xia, Wei‐Xiong; Shi, Jun‐Li; Ma, Wen‐Juan; Li, Yong; Ye, Yan‐Fang; Liang, Hu; Ke, Liang‐Ru; Lv, Xing; Yang, Jing; Xiang, Yan‐Qun; Guo, Xiang
Abstract: Background: For patients with nasopharyngeal carcinoma (NPC) who undergo re‐irradiation with intensity‐modulated radiotherapy (IMRT), lethal nasopharyngeal necrosis (LNN) is a severe late adverse event. The purpose of this study was to identify risk factors for LNN and develop a model to predict LNN after radical re‐irradiation with IMRT in patients with recurrent NPC. Methods: Patients who underwent radical re‐irradiation with IMRT for locally recurrent NPC between March 2001 and December 2011 and who had no evidence of distant metastasis were included in this study. Clinical characteristics, including recurrent carcinoma conditions and dosimetric features, were evaluated as candidate risk factors for LNN. Logistic regression analysis was used to identify independent risk factors and construct the predictive scoring model. Results: Among 228 patients enrolled in this study, 204 were at risk of developing LNN based on risk analysis. Of the 204 patients treated, 31 (15.2%) developed LNN. Logistic regression analysis showed that female sex ( P = 0.008), necrosis before re‐irradiation ( P = 0.008), accumulated total prescription dose to the gross tumor volume (GTV) ≥145.5 Gy ( P = 0.043), and recurrent tumor volume ≥25.38 cm 3 ( P = 0.009) were independent risk factors for LNN. A model to predict LNN was then constructed that included these four independent risk factors. Conclusions: A model that includes sex, necrosis before re‐irradiation, accumulated total prescription dose to GTV, and recurrent tumor volume can effectively predict the risk of developing LNN in NPC patients who undergo radical re‐irradiation with IMRT.